Gaya Mengajar Guru dengan Strategi Ekspositori pada Pembelajaran Sejarah - Sari Widya; Rustiyarso Rustiyarso; Haris Firmansyah (JURNAL PENA EDUKASI, 2024)
Abstract: This study aims to identify teachers' preparation for implementation and barriers to teaching using expository in class XI IPA 3 history lessons at SMAN 11 Pontianak. The exploration system used is qualitative with a descriptive approach. Data collection methods were collected through observations, interviews, and documentation of the history teacher, curriculum assistant, and her 11th-grade science three students—data analysis methods: data reduction, data donation, and conclusions. As a result of this study, (1) at the teacher's teaching preparation stage, using an expository strategy, the teacher makes a learning implementation plan (RPP), makes teaching materials in PowerPoint (PPT) format, and purchases equipment again before entering the class. (2) In the learning implementation phase, the teacher makes suggestions to the students, explains them systematically through questions and answers, and creates a learning evaluation. Teachers also walk around the classroom and hand out materials to invite students. (3) A teaching barrier for history teachers is the difficulty of managing students' concentration and maintaining their concentration in a hot classroom.Keywords: Expository strategy; History learning; teaching styleAbstrak: Penelitian ini bertujuan untuk mengidentifikasi persiapan pelaksanaan guru dan hambatan pengajaran menggunakan kelas Penjelasan Sejarah Kelas XI IPA 3 SMAN 11 Pontianak. Sis-tem eksplorasi yang digunakan adalah kualitatif dengan pendekatan deskriptif. Metode pengumpulan data dikumpulkan melalui observasi, wawancara, dan dokumentasi terhadap guru sejarah, asisten kurikulum, dan siswa kelas 11 IPA kelas III. Metode analisis data: reduksi data, donasi data, dan penarikan kesimpulan. Hasil penelitian (1), pada tahap persiapan pem-belajaran, guru menggunakan strategi eksplanasi untuk membuat rencana kinerja pembelaja-ran (RPP), membuat bahan ajar dalam format Powerpint (PPT), dan membuat ulang peralatan sebelum menghadiri kelas. Ternyata. kelas. (2) Pada tahap pelaksanaan pembelajaran, guru memberikan saran kepada siswa, menjelaskannya secara sistematis melalui tanya jawab, dan membuat evaluasi pembelajaran. Guru juga berkeliling kelas dan membagikan materi untuk merekrut siswa. (3) Kendala pengajaran bagi guru sejarah adalah sulitnya mengatur konsentra-si siswa dan mempertahankan konsentrasi di kelas yang panas.Kata kunci: gaya mengajar; pembelajaran Sejarah; strategi Ekspositori